A comparative study and counseling program for the OLMAT - Cosico, Elsa, FdCC (Animo Repository, 1974)
The first part of this study aims to determine whether or not the OLMAT, a mental ability test in the English language and standardized in the American culture, retains its established validity and reliability when administered in Pilipino at an all-girls Catholic High School. The Otis-Lennon Mental Ability Test, intermediate level form K, was administered to 70 first year high school girls at Canossa School, under two types of language administration, Pilipino and English. The testing procedure was test-retest, counter balancing the language of administration such that half of the subjects were tested in English first, while the other half was tested in Pilipino first. The procedure was then reversed, so that each subject underwent both test administrations. The statistical procedures used were the Sandler's A T-test, Pearson Product Moment Linear Correlation Coefficient Formula, Spearman-Brown Split-Half Odd-Even Formula, Kuder-Richardson Formula 20, and Translated-Version formula. It was found that the mean DIQ results did not differ significantly according to the language of administration. The Pilipino OLMAT score was a slightly better predictor of grade averages than the English OLMAT score. It as also found that the Spearman-Brown and Kuder-Richardson reliability indices of both the English and Pilipino tests were high. Based on the findings of the study, it was concluded that the OLMAT DIQs from both administrations were positively related to academic grades, with the Pilipino test having a greater positive relationship than the English test. The Pilipino version of the OLMAT seemed to be a more valid instrument than the English OLMAT for the assessment of the mental ability of first year high school students. Also, the OLMAT intermediate level Pilipino version can be used as an entrance test for incoming freshmen in high school and also as a predictor of high school achievement. The second part of the study aims to work-out and experiment on a school counseling program for underachievers for Canossa School based on the OLMAT and the Mooney Problem Check List survey. Underachievers were determined by comparing their academic grades with the OLMAT scores. The Mooney Problem Checklist was then administered to the 325 high school students. After analyzing the problems, a guidance program for the high school was proposed. The counselor together with the homeroom teachers worked with the students on either their developmental or crisis-oriented problems. Consultation with parents in groups were also done. It was found that both group A and group B underachievers made progress in their academic achievement after the counseling sessions. It was concluded that Teacher Groups were an interesting and dynamic approach to educational problems. Also, the OLMAT as an indicator of students' achievement can be used with the Mooney Problem Checklist to detect underachievers and to find the reasons for their underachievement.